The design of a blended learning course to develop conference presentation skills for postgraduate students in medicine - Corbett, John Blair (Letras, 2022)
The predominance of English as a scientific lingua franca and the pressure to raise the international ranking of Brazilian universities have increased the demand for support in developing a range of academic literacies in English, for example in areas such as presenting one’s research at international conferences. The challenges to delivering targeted support for the development of such literacies include limited space in the curriculum, negotiating regular meeting times for busy students and instructors, and the fact that large institutions often have geographically dispersed campuses. Blended learning offers a possible means of addressing these challenges in the flexibility afforded by course delivery that is partly face-to-face and partly online and asynchronous. This paper reports on the design, delivery and evaluation of two editions of a course in conference presentation skills, delivered to postgraduate students in the Faculty of Medicine at the University of Sao Paulo in 2018-19. The paper discusses the affordances, limitations and continuing challenges of blended learning in support of academic literacies designed to enhance medical students’ presentational skills in English.